Diversity and Abundance of Mosquitoes in selected areas of Dhaka: Implications for public health - Begum, Shefali; Ara Refa, Reffat; Islam, Md Aminul; Akter , Tangin; Sarna, Mohsina Alam (Bangladesh Journal of Zoology, 2025)
The observation on the diversity and abundance of mosquito species was conducted at 33 and 34 no. wards of Dhaka South City Corporation during March 2022 to February 2023. About 2297 mosquito larval samples of five species under three genera were recorded. Among five mosquito species Culex quinquefasciatus showed a high abundance (45%) and Aedes albopictus showed the lowest abundance (6%). Among the eight study spots, Aga Sadek Lane showed the highest abundance (15.06%) and Siddiq Bazar showed the lowest (8.23%). The Shannon diversity index H' was the highest (1.292) for Abdul Hadi Lane and the lowest (0.929) for Nazira Bazar, the Simpson index for diversity was the maximum (0.993) for the Siddiq Bazar and the minimum (0.978), for the Aga Sadek Lane, species evenness was the highest (0.049) at Aga Sadek Lane and the minimum was (0.039) at Siddiq Bazar, the highest community dominance was for Nazira Bazar (82.8%) and the lowest for Abdul Hadi Lane (64.2%). The representation of species richness was done using rarefaction curves. Canonical Correspondence Analysis (CCA) was used to find out the relationship with the abiotic factors of habitat water. This study also revealed the relationship between mosquito vectors and diseases especially the impact of the abundance of dengue vectors (Ae. aegypti and Ae. albopictus) on occurrence of dengue cases and deaths. Ae. aegypti and Ae. albopictus populations were in peak at the months of October and September, respectively. Cases and dies were the highest in the month of December when the whole procedure from larvae to the end of incubation period completes. Bangladesh J. Zool. 53(2): 185-199, 2025